The influence of acid surface treatment on the physical and mechanical properties of steel structure as a precursor for fiber metal laminate structure. - NG, EUNICE HUI RONG (IRC, 2020)
This project is to study sandwich fibre-reinforced plastic layer where metal layers are combined is known as Fibre Metal Laminate (FML), which is a family of hybrid composite structure. The advantage of a composite with hybrid nature, is that it inhibits the strength of two different constituents’ which are metal and fibre that are stack alternatively. FML are able to provide outstanding mechanical properties as compared to the conventional composite with its high strength and corrosion resistance. Surface treatment is one of the methods to improve adhesion between steel structure and fibre which affect the strength of fibre adversely by influencing the chemical structure of fibres and the chemical bonding with matrix will be enhance. Hence, the parameters such as concentration of acid, time taken of immersion, grade of sandpaper and temperature expose were studied to select the most optimum level of parameter by using Taguchi’s Method.